2018
DOI: 10.1021/acscentsci.7b00595
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymeric Materials in Degradable Electronic Devices

Abstract: Biodegradable electronics have great potential to reduce the environmental footprint of devices and enable advanced health monitoring and therapeutic technologies. Complex biodegradable electronics require biodegradable substrates, insulators, conductors, and semiconductors, all of which comprise the fundamental building blocks of devices. This review will survey recent trends in the strategies used to fabricate biodegradable forms of each of these components. Polymers that can disintegrate without full chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
352
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(355 citation statements)
references
References 75 publications
(226 reference statements)
1
352
0
2
Order By: Relevance
“…Bioresorbable polymers are mostly employed as substrate support for degradable devices and systems . Compared to all the above‐discussed materials, polymeric materials offer higher flexibility in tuning the dissolution timescale.…”
Section: Bioresorbable Materials and Dissolution Chemistrymentioning
confidence: 99%
“…Bioresorbable polymers are mostly employed as substrate support for degradable devices and systems . Compared to all the above‐discussed materials, polymeric materials offer higher flexibility in tuning the dissolution timescale.…”
Section: Bioresorbable Materials and Dissolution Chemistrymentioning
confidence: 99%
“…However, due to the mechanical incompliance and the possibility of toxicity of inorganic materials, biodegradable polymers based on naturally derived polymers and synthetic polymers became the field of intensive study . In a recent review reported by Feig et al, taking an example of a typical transistor structure, it provided thorough materials design considerations for the individual degradable components, including but not limited to electrodes (e.g., corrodible metals such as Fe and Mg), substrates (e.g., polylactic‐co‐glycolic acid (PLGA)), dielectrics (e.g., poly(glycerol sebacate) (PGS)) and semiconductor films . With the wide choices of materials to achieve degradability, research on transient wearable and skin‐like electronics are expected to burgeon.…”
Section: Skin‐inspired Multifunctional Interfacesmentioning
confidence: 99%
“…[135,136] In a recent review reported by Feig et al, taking an example of a typical transistor structure, it provided thorough materials design considerations for the individual degradable components, including but not limited to electrodes (e.g., corrodible metals such as Fe and Mg), substrates (e.g., polylactic-co-glycolic acid (PLGA)), dielectrics (e.g., poly(glycerol sebacate) (PGS)) and semiconductor films. [137] With the wide choices of materials to achieve degradability, research on transient wearable and skin-like electronics are expected to burgeon. For example, adopting a typical piezoresistive sensor-based structure, the pressure sensor composed of degradable tissue paper and polylactide (PLA) substrate was shown in Figure 9d,e.…”
Section: Self-healing and Biodegradabilitymentioning
confidence: 99%
“…OSCs with π‐conjugated structure, such as pentacene, poly(3‐hexylthiophene) (P3HT), and poly(3,4‐ethylenedioxythiophene):poly(styrene sulfonic acid) (PEDOT:PSS), were successfully synthesized and extensively applied in organic electronics for physical, chemical, and biological sensing . To realize active response to the external stimuli by OSCs, the organic thin‐film transistor (OTFT) architecture has been favorably adopted, resulting in enhanced responsivity due to the field‐effect amplification, excellent sensitivity, long‐term stability, appealing biodegradability, and mechanical flexibility . Based on the device architectures and operation principles, OTFTs can be categorized into two types, namely, organic field‐effect transistors (OFETs) and organic electrochemical transistors (OECTs) .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] To realize active response to the external stimuli by OSCs, the organic thin-film transistor (OTFT) architecture has been favorably adopted, resulting in enhanced responsivity due to the field-effect amplification, excellent sensitivity, long-term stability, appealing biodegradability, and mechanical flexibility. [11][12][13][14] Based on the device architectures and operation principles, OTFTs can be categorized into two types, namely, organic field-effect transistors (OFETs) and organic electrochemical transistors (OECTs). [8,15] OFET-based sensors based on biopolymers including PLA, cellulose, PDMS, and parylene to realize various applications in physical signals sensing and mechanical recognition.…”
Section: Introductionmentioning
confidence: 99%